2002
DOI: 10.1093/hmg/11.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of an autoimmunity susceptibility locus (AIS1) to chromosome 1p31.3-p32.2

Abstract: Generalized vitiligo is a common autoimmune disorder in which patchy loss of skin and hair pigmentation results from loss of pigment-forming melanocytes from the involved regions. Vitiligo occurs with a frequency of about 1% in most populations, and is highly associated with other autoimmune disorders, particularly Hashimoto thyroiditis. Most cases of vitiligo are sporadic, although some cases cluster in families, and the disorder is thought to be oligogenic in origin. We have studied a large family cluster in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 24 publications
3
97
1
Order By: Relevance
“…[10][11][12] Vitiligo can also develop as 36 Likewise, the autoimmune susceptibility loci AIS1, AIS2 and SLEV1 are associated with generalised vitiligo that occurs with other autoimmune conditions. [13][14][15] In contrast, generalised vitiligo that presents in individuals without other autoimmune disorders is associated with AIS3. [13][14][15] In the present study, the disease-associated PTPN22 1858T allele appears to be associated with generalised vitiligo that develops without the concomitant occurrence of other autoimmune diseases, suggesting that the basis of generalised vitiligo might still be autoimmune in nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] Vitiligo can also develop as 36 Likewise, the autoimmune susceptibility loci AIS1, AIS2 and SLEV1 are associated with generalised vitiligo that occurs with other autoimmune conditions. [13][14][15] In contrast, generalised vitiligo that presents in individuals without other autoimmune disorders is associated with AIS3. [13][14][15] In the present study, the disease-associated PTPN22 1858T allele appears to be associated with generalised vitiligo that develops without the concomitant occurrence of other autoimmune diseases, suggesting that the basis of generalised vitiligo might still be autoimmune in nature.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In contrast, generalised vitiligo that presents in individuals without other autoimmune disorders is associated with AIS3. [13][14][15] In the present study, the disease-associated PTPN22 1858T allele appears to be associated with generalised vitiligo that develops without the concomitant occurrence of other autoimmune diseases, suggesting that the basis of generalised vitiligo might still be autoimmune in nature. The finding that the 1858T allele of the PTPN22 R620W polymorphism is associated with generalised vitiligo and other autoimmune conditions supports the hypothesis that there are common genetic variants that contribute to general immune-dysregulation and susceptibility to autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a whole genome scan of a large family cluster with both vitiligo and Hashimoto thyroiditis, a general autoimmune susceptibility locus (AIS1) was mapped to human chromosome 1, and evidence was reported for a Hashimoto disease susceptibility locus within a chromosome 6 region spanning both the MHC and AIDT1, a non-MHC locus associated with susceptibility to both Hashimoto thyroiditis and Graves' disease. 24 A linkage disequilibrium analysis of 56 multigeneration Columbian families with vitiligo using microsatellite markers spanning the entire human MHC region revealed a major genetic factor within the MHC at 6p21.3-21.4, with a dominant mode of inheritance in vitiligo patients with an early age of onset and a recessive mode of inheritance influenced by environmental effects in vitiligo patients with an age of onset after 30 years of age. 10 Comparisons of a variety of inheritance models suggested that the most parsimonious genetic model was that of a major 10 Many other HLA associations have been reported between specific alleles of complement, class I and class II MHC genes with vitiligo in various ethnic and racial subpopulations (reviewed in Friedmann 9 ), but no common HLA association is observed.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Vitiligo susceptibility does not follow a simple Mendelian inheritance pattern, and much of the available data support the hypothesis that vitiligo is a complex hereditary disease influenced by a set of recessive alleles occurring at several unlinked autosomal loci that collectively confer the vitiligo phenotype. [22][23][24] Vitiligo may therefore be considered a polygenic disease, with alleles at multiple loci possibly contributing to increased susceptibility to and/or direct pathogenesis of vitiligo. We have recently reported association of the catalase gene and vitiligo susceptibility in support of the self-destruct model of vitiligo pathogenesis.…”
Section: Introductionmentioning
confidence: 99%